Sulfonated polyphenylene-b-polyimide, proton exchange membrane, preparation method and application

The preparation of sulfonated polyphenylene-b-polyimide block copolymers via palladium-catalyzed Suzuki cross-coupling reaction solved the mechanical properties and proton conduction problems of sulfonated polyphenylene proton exchange membranes under high temperature and low humidity conditions, enabling efficient operation of fuel cells in high temperature and low humidity environments.

CN120923742APending Publication Date: 2025-11-11SHANGHAI JIAOTONG UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511156966.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-18
Publication Date
2025-11-11

AI Technical Summary

Technical Problem

Existing sulfonated polyphenylene proton exchange membranes suffer from poor mechanical properties, low fuel cell output power under high temperature and low humidity conditions, and short service life, making it difficult to meet the performance requirements of fuel cells.

Method used

Sulfonated polyphenylene-b-polyimide block copolymers were prepared by palladium-catalyzed Suzuki cross-coupling reaction of amino-terminated sulfonated polyphenylene oligomers and anhydride-terminated polyimide oligomers. The chemical structures of hydrophilic and hydrophobic blocks were controlled to form a distinct microphase separation structure, thereby improving proton conduction and mechanical properties.

Benefits of technology

Under high temperature and low humidity conditions, the proton exchange membrane maintains a high output power density and resistance to free radical oxidation, thereby improving the electrochemical performance and durability of the fuel cell.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120923742A_ABST
    Figure CN120923742A_ABST
Patent Text Reader

Abstract

The invention discloses an amino-terminated sulfonated polyphenylene oligomer and a preparation method thereof. A sulfonated polyphenylene-b-polyimide copolymer is prepared from the amino-terminated sulfonated polyphenylene oligomer and an anhydride-terminated polyimide oligomer by adopting a block copolymerization method. By regulating and controlling the lengths of a hydrophilic block and a hydrophobic block, the sulfonated polyphenylene-b-polyimide membrane material is endowed with excellent hydrolytic stability, relatively high oxidation stability and an optimized microcosmic phase separation structure, so that the formation of a continuous water channel is facilitated; the problem that the sulfonated polyphenylene copolymer is poor in power generation efficiency under the conditions of high temperature and low relative humidity is effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of proton exchange membrane technology, and particularly relates to a sulfonated polyphenylene- b - Polyimide, proton exchange membrane, preparation method and application. Background Technology

[0002] Fuel cells are efficient and clean energy conversion devices. Among them, proton exchange membrane fuel cells (PEMFCs) have broad application prospects in electric vehicles, portable electronic devices, home distributed power generation systems, and aerospace due to their advantages such as high energy conversion efficiency, low environmental pollution, and low operating noise. Especially in the electric vehicle sector, PEMFCs help reduce dependence on petroleum resources and promote the development of sustainable energy, which is of significant strategic importance. As the core component of fuel cells, the performance and stability of the proton exchange membrane directly affect the electrochemical performance, efficiency, and lifespan of the fuel cell. To meet practical application requirements, the proton exchange membrane should meet the following basic requirements: 1) low cost; 2) high proton conductivity; 3) high mechanical strength and toughness; 4) low swelling ratio; 5) excellent chemical stability; 6) low fuel and oxygen permeability; 7) good thermal stability. Currently, the commercially available proton exchange membrane is Nafion, manufactured by DuPont. ® Perfluorosulfonic acid membranes are the most typical. These membranes possess excellent chemical stability and high proton conductivity, and are widely used in low-temperature fuel cells. However, Nafion… ® The membrane still suffers from the following drawbacks: 1) high cost; 2) limited operating temperature; 3) high swelling rate; 4) high fuel permeability; and 5) poor water retention at high temperatures. These problems severely limit Nafion's development. ® Further applications in fuel cells. To this end, researchers have conducted extensive research on non-fluorinated sulfonated aromatic polymer materials in recent years, focusing on developing low-cost sulfonated hydrocarbon polymer proton exchange membranes with tunable structures to improve the durability and proton conductivity of membrane materials, thereby replacing existing perfluorosulfonic acid proton exchange membrane materials.

[0003] Sulfonated polyphenylene and its derivatives are considered to be among the most promising candidate materials because their main chain is a fully aromatic structure and lacks chemically degradable heteroatom bonds (such as ether bonds, sulfur bonds, etc.). However, they have disadvantages such as poor solvent solubility, insufficient film-forming ability, and poor mechanical strength. Currently, two main synthesis strategies are used to improve the film-forming ability and mechanical properties of sulfonated polyphenylene film materials: (1) copolymerizing sulfonated aromatic units with hydrophobic aromatic units to control the length of the polyphenylene main chain. l p(1) or conformational behavior; (2) introduce flexible side chains or side groups with larger volume. The main methods for synthesizing sulfonated polyphenylene polymers include Diels-Alder reaction, nickel-catalyzed CC coupling polymerization, nickel-catalyzed Grignard chain growth coupling polymerization, Cu-catalyzed Ullmann reaction, and Pd-catalyzed Suzuki cross coupling reaction. The ratio of para and meta positions of benzene rings in the main chain of sulfonated polyphenylene prepared by Diels-Alder reaction is difficult to determine, resulting in uncertainty in the chemical structure of the polymer. Nickel-catalyzed CC coupling polymerization requires anhydrous and oxygen-free conditions and is incompatible with many nucleophilic groups, so the experimental conditions are extremely strict. Cu-catalyzed Ullmann reaction is extremely sensitive to the electronic environment around the carbon atoms of halogens in the substrate, and the types of monomers that can be used to prepare high molecular weight polymers are limited. Furthermore, the main chain of sulfonated polyphenylene prepared by the above three methods is highly rigid and the distribution of sulfonic acid groups in the polymer chain is difficult to control precisely. The separation of ionic / nonionic phases in sulfonated polyphenylene films is not obvious, which means that sulfonated aromatic polymers usually require a high ion exchange capacity (IEC) to obtain suitable proton conductivity. This increases the water absorption of the membrane, thereby significantly reducing the mechanical properties of the membrane.

[0004] Block copolymers possess the ability to form nanophase-separated structures due to the thermodynamic incompatibility between different blocks. Sulfonated polyphenylene block copolymer proton exchange membranes prepared via nickel-catalyzed Grignard chain growth coupling polymerization and Pd-catalyzed Suzuki cross-coupling reaction can form clear hydrophilic nanochannels through nanophase separation, thereby achieving rapid proton transport. This significantly improves the proton conductivity of sulfonated aromatic polyelectrolyte membranes and reduces their dependence on humidity changes under low relative humidity conditions. However, limited by the synthesis methods and strategies, the prepared sulfonated polyphenylene backbone has high rigidity and low molecular weight, resulting in relatively low mechanical properties of the membrane. The poly(5'-hexyloxy-1',4-biphenyl)-b-poly(2',4'-dipropoxysulfonate-1',4-biphenyl) proton exchange membrane prepared by JinK et al. has a tensile strength of less than 10 MPa and an elongation at break of less than 10%, which is insufficient to meet the performance requirements of proton exchange membranes in fuel cells. Therefore, there are still huge challenges in preparing sulfonated polyphenylene block copolymer proton exchange membranes with strong mechanical properties, high power generation efficiency, and excellent durability.

[0005] Constructing well-defined ion channel structures is crucial for improving the transport performance of PEMs. Therefore, developing new material design strategies will be a key next step in advancing the application of polyphenylene ionomers in fuel cell membranes. Polynaphthaleneimide (PI) has attracted widespread attention due to its low cost, high mechanical strength, excellent thermal stability, strong gas barrier properties, and tunable chemical structure. This study synthesizes sulfonated polyphenylene with a precise chemical structure using amino-terminated sulfonated polyphenylene as a hydrophilic block and anhydride-terminated polyimide as a hydrophobic block. b - Polyimide block copolymers can regulate the distribution of sulfonic acid groups in block polymers, thereby adjusting the chemical structure of polymers while maintaining the excellent chemical stability of sulfonated polyphenylene, improving film-forming ability, and enhancing the degree of microphase separation. Summary of the Invention

[0006] To address the problems of poor mechanical properties, low fuel cell output power under high temperature and low humidity conditions, and short service life of sulfonated polyphenylene proton exchange membranes in the prior art, this invention provides a proton exchange membrane material with excellent comprehensive performance. It improves the mechanical properties and dimensional stability of sulfonated polyphenylene proton exchange membranes and enhances their proton conduction performance under high temperature and low relative humidity conditions, thereby improving the electrochemical performance and durability of fuel cells.

[0007] To achieve the above objectives, this invention provides a method for synthesizing amino-terminated sulfonated polyphenylene oligomers, and further prepares a class of sulfonated polyphenylene- b - Polyimide block copolymer proton exchange membrane. This copolymer membrane material exhibits good phase separation morphology, excellent mechanical properties, and proton conductivity. Fuel cells assembled based on this membrane can maintain high output power density and good resistance to free radical oxidation under high temperature and low relative humidity conditions, showing broad application prospects and significant engineering promotion value.

[0008] In a first aspect, the present invention provides an amino-terminated sulfonated polyphenylene oligomer with the structural formula shown in formula (1):

[0009] Equation (1)

[0010] in, R1 represents an aromatic substituent containing at least one sulfonic acid group (-SO3H) or its salt form, wherein the aromatic substituent comprises a carbonyl group (-CO-) and / or a sulfonyl group (-SO2-). R2 and R3 represent monovalent groups, which are selected from hydrogen, halogen, alkyl or substituted alkyl, aryl or substituted aryl; x is an integer from 1 to 100, representing the number of repeating units; y is an integer from 1 to 4, representing the number of R2 groups in the benzene ring; Preferably, R1 is selected from any one of the following groups: , , , , , , , .

[0011] Preferably, R2 is selected from any one of the following groups: -H, -CH3, -CF3.

[0012] Preferably, R3 is selected from any one of the following groups: -H, -CH3, -F.

[0013] Unless otherwise specified, the meanings of the symbols in the following text are the same as those described above.

[0014] In a second aspect, the present invention provides a method for preparing amino-terminated sulfonated polyphenylene oligomers, comprising the following steps: Step 1) Sulfonated dibromobiphenyl compound containing carbonyl or sulfonyl groups, diboronic acid compound or its esterified derivative, end-capping agent containing amino groups, base, palladium (Pd) catalyst, organic solvent and water are added sequentially to a three-necked flask and reacted at 20~150℃ for 1~30 hours. The reaction process is shown in reaction formula (1) to obtain amino-terminated polyphenylene oligomers with sulfonated aromatic side chains. Step 2): After cooling the reaction system to room temperature, remove some of the solvent under reduced pressure. Add the concentrated solution dropwise to a poor organic solvent to induce product precipitation. After washing with the poor solvent and centrifugation, dry under vacuum at 10–100 °C. The resulting solid is dissolved in a mixed solvent and then subjected to H₂O₂… + Amberlite cation exchange resin was used for cation exchange to obtain a sulfonic acid polymer; the filtrate was collected after vacuum filtration, and an organic base was added dropwise to the filtrate to obtain a sulfonated triethylamine salt polymer; most of the solvent in the resulting reaction solution was removed by vacuum distillation, and the concentrate was added dropwise to a poor organic solvent. The precipitated solid was washed, centrifuged, and then vacuum dried at 10-100 °C for 12 hours to obtain the amino-terminated sulfonated polyphenylene oligomer.

[0015] Reaction formula (1)

[0016] in, R1 represents an aromatic substituent containing at least one sulfonic acid group (-SO3H) or its salt form, wherein the aromatic substituent comprises a carbonyl group (-CO-) and / or a sulfonyl group (-SO2-). R2 and R3 represent monovalent groups, which are selected from hydrogen, halogen, alkyl or substituted alkyl, aryl or substituted aryl; x is an integer from 1 to 100, representing the number of repeating units; y is an integer from 1 to 4, representing the number of R2 groups in the benzene ring; R4 represents a monovalent group, which is selected from boric acid groups or their esterified, salted, coordinated or other derivative forms; Preferably, R4 is selected from one or more of the following groups: , , , , .

[0017] This invention employs a palladium-catalyzed Suzuki cross-coupling reaction under an inert gas atmosphere to prepare amino-terminated sulfonated polyphenylene hydrophilic blocks with adjustable block lengths.

[0018] In some embodiments, in step 1), the sulfonated dibromobiphenyl compound containing a carbonyl or sulfonyl group is in the form of a sodium sulfonate salt.

[0019] In some embodiments, in step 1), the diboronic acid compound or its esterified derivative is selected from one or more of terephthaloboronic acid, pinacol terephthaloate, ethylene glycol terephthaloate, catechol terephthaloate, propylene glycol terephthaloate, isophthaloboronic acid, pinacol terephthaloate, pinacol terephthaloate, terephthaloboronic acid, (2-methyl-1,4-phenyl)diboronic acid, (2-methyl-1,4-phenyl)diboronic acid dipinacol ester, and 5-(trifluoromethyl)benzene-1,3-diboronic acid.

[0020] In some embodiments, in step 1), the amino-containing capping agent is selected from one or more of 4-aminophenylboronic acid salt, 4-aminophenylboronic acid pinacol ester, 4-aminophenylboronic acid, 3-aminophenylboronic acid pinacol ester, 3-aminophenylboronic acid, and 2-fluoro-5-aminophenylboronic acid.

[0021] In some embodiments, in step 1), the organic solvent is selected from... N , N -Dimethylacetamide, N , N -Dimethylformamide, N One or more of the following: methylpyrrolidone, dimethyl sulfoxide, methanol, ethanol, tetrahydrofuran, and toluene.

[0022] In some embodiments, in step 1), the palladium (Pd) catalyst is selected from one or more of Pd(OAc)2, Pd(PPh3)4, and Pd(dppf)Cl2. The present invention preferably uses palladium acetate, which is insensitive to oxygen, as the catalyst, allowing for feeding operations in a reaction apparatus without a glove box.

[0023] In some embodiments, in step 1), the base is selected from one or more of Na2CO3, K2CO3, K3PO4, triethylamine, tetramethylammonium hydroxide, and tetrabutylammonium hydroxide.

[0024] In some embodiments, in step 1), the palladium (Pd) catalyst may or may not use a ligand. The ligand is selected from one or more of PPh3, n-Bu3P, 1,2-bis(diphenylphosphine)ethane, 1,3-bis(diphenylphosphine)propane, and 1,1'-bis(diphenylphosphine)ferrocene. The molar ratio of the ligand to a sulfonated dibromobiphenyl compound containing a carbonyl or sulfonyl group is 0:1 to 1:1.

[0025] In some embodiments, in step 1), the molar ratio of the base to the sulfonated dibromobiphenyl compound containing a carbonyl or sulfonyl group is 0:1 to 20:1; the molar ratio of the Pd catalyst to the sulfonated dibromobiphenyl compound containing a carbonyl or sulfonyl group is 0:1 to 1:1; the volume ratio of the organic solvent to water is 0:1 to 100:1; and the solid content of the reaction system is 0.1 to 100% (mass / volume percentage, w / v%).

[0026] In some embodiments, in step 2), the H in the Amberlite ion exchange resin + The molar ratio of the sulfonic acid group to the sulfonic acid group is 1:1 to 20:1; the solid content of the reaction solution is 0.1 to 100% (mass / volume percentage, w / v%).

[0027] In some embodiments, in step 2), the organic base is selected from one or more of triethylamine, tetramethylammonium hydroxide, and tetrabutylammonium hydroxide.

[0028] In some embodiments, in step 2), the molar ratio of the organic solvent to water in the mixed solvent is 0:1 to 100:1, and the organic solvent is selected from... N , N -Dimethylacetamide, N , N -Dimethylformamide, N One or more of methylpyrrolidone, dimethyl sulfoxide, methanol, ethanol, tetrahydrofuran, and toluene are selected. This invention selects a suitable organic solvent / water mixed solvent ratio to ensure complete dissolution of the hydrophilic block in the form of sodium sulfonate, thereby preparing hydrophilic blocks with controllable block lengths.

[0029] In some embodiments, in step 2), the unsuitable organic solvent is selected from one or more of acetone, isopropanol, ethyl acetate, methanol, ethanol, tetrahydrofuran, and toluene.

[0030] In a third aspect, the present invention provides a sulfonated polyphenylene- b - A polyimide copolymer, the structural formula of which is represented by Formula 2:

[0031] (Equation 2)

[0032] in, m and n are integers from 1 to 100, representing the number of repeating units; Ar1 represents a tetravalent group, which is selected from naphthyl or naphthalene derivatives; R5 represents a divalent group, which is selected from aliphatic groups, aromatic groups, or aromatic-aliphatic groups; Preferably, R5 is selected from any one of the following groups: , , , , .

[0033] Preferably, Ar1 is selected from any one of the following groups: , , .

[0034] Unless otherwise specified, the meanings of the symbols in the following text are the same as those described above.

[0035] In a fourth aspect, the present invention provides a sulfonated polyphenylene- b The preparation method of the polyimide copolymer includes the following steps: Step (1): Ar1 type dianhydride monomer, hydrophobic R5 type diamine monomer, catalyst and phenolic good solvent are added to a three-necked flask and heated to 50~140 ℃ for 1~10 hours. The reaction temperature is then increased to 150~200 ℃ for 2~30 hours. After the resulting reaction system is cooled to room temperature, it is added dropwise to an organic poor solvent to promote the precipitation of the product. After washing with the poor solvent and centrifugation, it is vacuum dried at 10~200 ℃ to obtain anhydride-terminated polyimide oligomer. The reaction process is shown in reaction formula (2):

[0036] Reaction formula (2); Step (2): The amino-terminated sulfonated polyphenylene oligomer, the anhydride-terminated polyimide oligomer, the catalyst, and a good phenolic solvent are added to another three-necked flask. The mixture is heated at 50-140 °C for 1-10 hours. Subsequently, the temperature is increased to 150-200 °C, and the reaction continues for 2-30 hours. After the resulting reaction system is cooled to room temperature, a poor organic solvent is added dropwise to promote the precipitation of the product. After washing with the poor solvent and centrifugation, the product is dried under vacuum at 10-200 °C to obtain sulfonated polyphenylene- b - Polyimide block copolymer, the reaction process is shown in reaction formula (3):

[0037] Reaction formula (3).

[0038] In some embodiments, in steps (1) and (2), the organic poor solvent is selected from one or more of methanol, ethanol, isopropanol, acetone or ethyl acetate.

[0039] In some embodiments, in step (1), the molar ratio of the Ar1 type dianhydride monomer to the hydrophobic R5 type diamine monomer is greater than 1; in step (2), the molar ratio of the amino-terminated sulfonated polyphenylene oligomer to the anhydride-terminated polyimide oligomer is equal to 1.

[0040] In some embodiments, in steps (1) and (2), the phenolic solvent is selected from one or more of m-cresol, o-cresol, p-cresol, m-chlorocresol, o-chlorocresol, or p-chlorocresol.

[0041] In some embodiments, in steps (1) and (2), the catalyst is selected from one or more of acetic acid, benzoic acid, chlorobenzoic acid, hydroxybenzoic acid, quinoline, isoquinoline or pyridine.

[0042] In some embodiments, in step (1), the solid content of the anhydride-terminated polyimide oligomer in a good phenolic solvent is 5-40 w / v%; in step (2), the sulfonated polyphenylene- b The solid content of the polyimide block copolymer in good phenolic solvents is 0.5~25 w / v.

[0043] This invention employs amino groups to cap hydrophilic blocks. These capping groups can polymerize with anhydride-capped hydrophobic blocks of different chemical structures, thereby improving the film-forming properties and phase separation of the proton exchange membrane by controlling the chemical structures of the hydrophilic and hydrophobic blocks. The prepared sulfonated polyphenylene- b- Polyimide has a precisely controllable hydrophilic block length, high molecular weight, and good film-forming properties.

[0044] In a fifth aspect, the present invention provides a solution composed of the sulfonated polyphenylene- b A proton exchange membrane made of polyimide block copolymer, wherein sulfonated polyphenylene- b A film was prepared from a polyimide block copolymer, and the film was subjected to proton exchange treatment to obtain a film composed of sulfonated polyphenylene- b - A proton exchange membrane made of polyimide block copolymer.

[0045] In some embodiments, the film formation includes: applying the sulfonated polyphenylene... b - Polyimide block copolymers dissolved in good phenolic solvents form sulfonated polyphenylene- b A polyimide block copolymer solution was prepared, and then the solution was uniformly coated onto the surface of a glass plate and dried at a temperature of 90~110 ℃ for 5~15 hours to obtain a film; the film was then peeled off from the glass plate.

[0046] In some embodiments, the proton exchange process involves immersing the membrane in alcohol to remove residual solvent from the membrane, followed by immersing the membrane in a protic acid solution for proton exchange.

[0047] In some embodiments, the proton-exchanged membrane is washed with water until neutral, and then vacuum dried at a temperature of 50-150 °C for 2-30 hours.

[0048] In a sixth aspect, the present invention provides a solution of sulfonated polyphenylene- b Application of proton exchange membranes made of polyimide block copolymers in batteries. These batteries include, but are not limited to, fuel cells.

[0049] Technical effect

[0050] This invention employs a palladium-catalyzed Suzuki cross-coupling reaction under an inert gas atmosphere to design and synthesize a novel class of sulfonated polyphenylene hydrophilic blocks with a conjugated backbone structure free of ether bonds, the block length of which is controllable. Furthermore, sulfonated polyphenylene-... is prepared via block copolymerization using flexible long-chain polyimides as hydrophobic blocks. b - Polyimide copolymers effectively solve the problem of poor power generation efficiency of sulfonated polyphenylene copolymers under high temperature and low relative humidity conditions.

[0051] This invention introduces a flexible hydrophobic diamine monomer and employs a block copolymerization strategy to regulate the hydrophilic and hydrophobic distribution of polymer segments, resulting in a more ordered spatial arrangement of sulfonic acid groups within the polymer chain, thereby enhancing the microscopic phase separation of the material. This method helps to construct a more continuous and structurally stable water channel network within the membrane, improving the membrane's proton conductivity in low-humidity environments. The phase separation enhancement mechanism is as follows: the copolymer designed in this invention consists of sulfonated polyphenylene hydrophilic blocks and flexible polyimide hydrophobic blocks, with a significant difference in polarity between the two, resulting in a high Flory-Huggins interaction parameter (χ). Under appropriate polymerization conditions, this system... χ When the N value exceeds the critical value for microphase separation, the block copolymer undergoes thermodynamic spontaneous phase separation at the nanoscale, forming distinct hydrophilic and hydrophobic phase regions. Fuel cells fabricated using proton exchange membranes maintain high output power under low relative humidity (≤30% RH) conditions.

[0052] This invention imparts the following properties to membrane materials by controlling the lengths of hydrophilic and hydrophobic blocks: Excellent hydrolytic stability: It maintains the integrity of the main chain structure even under high temperature and high humidity conditions; High oxidative stability: It has strong resistance to free radical oxidative degradation; Optimized microphase separation structure: facilitates the formation of continuous water channels and enhances proton conduction performance under low humidity conditions.

[0053] This structural design concept can be extended to various sulfonated polyphenylene block copolymer systems, and has good technical versatility and potential for iterative development.

[0054] The synthetic route of this invention is based on scalable sulfonated aryldibromobiphenyl monomers and commercially available aryl diboronic acid as a starting material. The synthetic steps can be successfully implemented under laboratory and pilot-scale conditions. The Suzuki-Miyaura coupling reaction and polyimide condensation process used are mature, controllable, and easily scaled up, possessing the following industrialization advantages: The monomers used are inexpensive, and the synthesis route is environmentally friendly; It can be smoothly replaced based on existing membrane production lines (solution casting or extrusion); The membrane material has high physical strength and good machinability, and can be directly applied to membrane electrode assemblies (MEAs). The technology route can be extended to other aromatic backbone copolymers, which is conducive to technology licensing and horizontal expansion.

[0055] In addition, this membrane material is particularly suitable for fuel cell systems operating under high temperature and low humidity conditions, such as: on-board fuel cells without external humidification systems (suitable for commercial vehicles and heavy trucks); aerospace power systems; and has good application compatibility and market substitution potential.

[0056] The sulfonated polyphenylene provided by this invention b Polyimide proton exchange membrane materials have significant advantages in structural design, comprehensive performance, and feasibility of preparation processes. They possess the technological foundation for a closed loop from laboratory to industrial scale-up and can be widely used in next-generation high-performance fuel cell systems. Attached Figure Description

[0057] Figure 1 The amino-terminated sulfonated polyphenylene oligomers (a) S5 and (b) S5 prepared in Examples 1 and 2 of this invention are examples of amino-terminated sulfonated polyphenylene oligomers prepared in this invention. 10 of 1 HNMR spectrum (solvent: DMSO-d6); Figure 2 This is Embodiment 3 of the present invention (NS5-) b -(ND) 10 Example 4 ((NS5)2- b -(ND) 10 Example 5 (S) 10 - b -(ND) 10 Example 6 (S) 10 - b -(ND)8) and Example 7 (S) 10 - b Infrared absorption spectrum of -(ND)6); Figure 3 This is Embodiment 3 of the present invention (NS5-) b -(ND) 10 Example 4 ((NS5)2- b -(ND) 10 Example 5 (S) 10 - b -(ND) 10 Example 6 (S) 10 - b -(ND)8), Example 7 (S) 10 - b X-ray diffraction (XRD) patterns of (ND)6 and Nafion 212; Figure 4 This is Embodiment 6 (S) of the present invention. 10 - b Transmission electron microscopy (TEM) image of (ND)8; Figure 5-1 This is Embodiment 6 (S) of the present invention. 10 - b Polarization curves of single cells assembled with (ND)8 and Nafion 212 at 90 °C, back pressure 150 kPa and relative humidity 100%; Figure 5-2 This is Embodiment 6 (S) of the present invention. 10 - b Polarization curves of single cells assembled with (ND)8 and Nafion 212 at 90 °C, back pressure 150 kPa and relative humidity 30%; Figure 6 This is Embodiment 6 (S) of the present invention. 10 - b Single cells assembled with (ND)8 and Nafion 212 were tested for OCV (open-circuit voltage) durability at 90 °C, 0 kPa back pressure and 50% relative humidity. Figure 7 This is Embodiment 3 of the present invention (NS5-) b -(ND) 10 Example 4 ((NS5)2- b -(ND) 10 Example 5 (S) 10 - b -(ND) 10 Example 6 (S) 10 - b -(ND)8), Example 7 (S) 10 - b -(ND)6) stress-strain curve. Detailed Implementation

[0058] The technical solution of the present invention will be further illustrated by the following specific embodiments, but these should not be considered as limiting the scope of protection of the present invention. Any modifications, equivalent substitutions, or variations made without departing from the concept of the present invention should be considered as included within the scope of protection of the present invention.

[0059] In this invention, all operations involving easily oxidized or hydrolyzed raw materials are performed under nitrogen protection. Unless otherwise stated, all raw materials used in this invention are commercially available, or prepared using any method known in the art, or prepared according to the methods provided in this invention.

[0060] Example 1: Synthesis of amino-terminated polyphenylene oligomer S5

[0061] Synthesis of S5: Under nitrogen protection, sodium 3,3'-(4,4'-dibromo-[1,1'-biphenyl]-2,2'-dicarbonyl)diphenylsulfonate (724.3 mg, 1.0 mmol), pinacol terephthaloate (264.2 mg, 0.8 mmol), 4-aminophenylborate salt (92.0 mg, 0.4 mmol), 1 M Na2CO3 aqueous solution (4 mL), DMAc (9.5 mL), and Pd(OAc)2 (0.067 g) were added sequentially to a 100 mL three-necked flask. The reaction system was subjected to a freeze-evacuation-thawing cycle three times to remove oxygen, followed by heating to 85 °C and stirring for 24 hours. After cooling to room temperature, 3 / 4 of the solvent was removed under reduced pressure. The concentrated solution was added dropwise to acetone to induce product precipitation. After washing with acetone, centrifugation, and vacuum drying at 50 °C, the product was obtained. The resulting solid was dissolved in DMAc / H2O (10 mL / 10 mL), and then precipitated with 6 mL of H2O. + The cation exchange was performed three times using Amberlite cation exchange resin to obtain a sulfonic acid polymer. The filtrate was collected after vacuum filtration, and triethylamine (404 mg, 4 mmol) was added dropwise to the filtrate to obtain a sulfonated triethylamine salt polymer. The resulting solution was subjected to rotary evaporation under reduced pressure to remove 3 / 4 of the solvent. The concentrated solution was added dropwise to isopropanol, and the precipitated solid was washed, centrifuged, and then vacuum dried at 50 °C for 12 hours. Product S was obtained in 50.680 g, with a yield of 85%.

[0062] Example 2: Amino-terminated polyphenylene oligomer S 10 Synthesis

[0063] S 10 Synthesis: Under nitrogen protection, sodium 3,3'-(4,4'-dibromo-[1,1'-biphenyl]-2,2'-dicarbonyl)diphenylsulfonate (724.3 mg, 1.0 mmol), pinacol terephthaloate (297.0 mg, 0.9 mmol), 4-aminophenylborate salt (43.8 mg, 0.2 mmol), Na₂CO₃ (424.0 mg, 4 mmol), water (6.3 mL), DMAc (14.7 mL), and Pd(OAc)₂ (0.067 g) were added sequentially to a 100 mL three-necked flask. The reaction system was subjected to a freeze-evacuation-thawing cycle three times to remove oxygen, followed by heating to 85 °C and stirring for 24 hours. After cooling to room temperature, 3 / 4 of the solvent volume was removed under reduced pressure. The concentrated solution was added dropwise to acetone to induce product precipitation. After washing with acetone, centrifugation, and vacuum drying at 50 °C, the product was obtained. The resulting solid was dissolved in DMAc / H2O (10 mL / 10 mL), and then precipitated with 6 mL of H2O. +The Amberlite cation exchange resin was subjected to cation exchange three times to obtain a sulfonic acid polymer. The filtrate was collected after vacuum filtration, and triethylamine (404.0 mg, 4 mmol) was added dropwise to the filtrate to obtain a sulfonated triethylamine salt polymer. The resulting solution was subjected to rotary evaporation under reduced pressure to remove 3 / 4 of the solvent. The concentrated solution was added dropwise to isopropanol, and the precipitated solid was washed, centrifuged, and then vacuum dried at 50 °C for 12 hours to obtain product S. 10 0.650 g, yield 81%.

[0064] The amino-terminated sulfonated polyphenylene oligomers (a) S5 and (b) S5 prepared in Examples 1 and 2 10 of 1 H NMR spectrum as shown Figure 1 As shown, the solvent is DMSO-d6.

[0065] Example 3 NS5- b -(ND) 10 Block copolymer proton exchange membrane

[0066] Under nitrogen protection, 1,4,5,8-naphthalenetetracarboxylic anhydride (NTDA) (2.9500 g, 11 mmol), 1,12-diaminododecane (DDA) (2.0040 g, 10 mmol), benzoic acid (2.6870 g, 22 mmol), 3.0 mL isoquinoline, and 40 mL m-cresol were sequentially added to a 100 mL dry three-necked flask. The mixture was stirred at room temperature for 1 hour, then heated to 80 °C for 4 hours, and then heated to 180 °C for another 20 hours. After the reaction was complete, the mixture was cooled to room temperature, and the reaction system was slowly poured into 150 mL of methanol, precipitating an orange solid powder. The obtained solid was repeatedly washed with methanol, filtered, and then extracted with acetone until the eluent was colorless. Finally, it was dried under vacuum at 160 °C for 20 hours to obtain a polyimide oligomer (ND) with an anhydride-terminated repeating unit length of 10. 10 .

[0067] Under nitrogen protection, S5 (2.0515 g, 0.5 mmol), 1,4,5,8-naphthalenetetracarboxylic anhydride (NTDA) (0.0670 g, 0.25 mmol), benzoic acid (0.0610 g, 0.5 mmol), isoquinoline (0.0646 g, 0.5 mmol), and 10 mL of m-cresol were sequentially added to a 100 mL dry three-necked flask. The mixture was mechanically stirred at room temperature for 1 hour, then slowly heated to 80 °C for 4 hours, and then heated to 180 °C for another 4 hours to obtain the amino-terminated hydrophilic block NS5. Subsequently, (ND) synthesized in the previous step was added to the three-necked flask. 10(1.1483 g, 0.25 mmol), benzoic acid (0.0610 g, 0.5 mmol), isoquinoline (0.0646 g, 0.5 mmol), and 10 mL m-cresol. The resulting reaction system was mechanically stirred at room temperature for 1 hour, then slowly heated to 80 °C for 4 hours, and then heated to 180 °C for another 20 hours. After the reaction was complete, the resulting reaction system was cooled to room temperature, and the resulting mixture was stirred at room temperature for 1 hour, followed by heating to 180 °C for 20 hours. After the reaction was complete, the resulting mixture was cooled to 80 °C and quickly poured into 150 mL of methanol, forming a filamentous precipitate. The precipitate was repeatedly washed with methanol and filtered to collect the solid product. Finally, the solid product was vacuum dried at 100 °C for 20 hours to obtain crystalline sulfonated polyphenylene with an average hydrophobic block length of 10 and a hydrophilic block of NS5. b -Polyimide block copolymer NS5- b -(ND) 10 .

[0068] NS5- b -(ND) 10 The polymer solution was prepared by dissolving it in m-cresol to a solid content of 5 w / v. After vacuum degassing, the resulting solution was cast onto a clean glass plate and dried in a 110 °C oven for 5 hours to form a polymer film. After drying, the film was peeled off the glass plate and immersed in methanol for 24 hours to remove residual m-cresol. Subsequently, the film was placed in 50 mL of 1.0 M sulfuric acid solution and immersed at room temperature for 72 hours for proton exchange treatment. The proton-exchanged film was washed with deionized water until neutral and then vacuum dried at 120 °C for 20 hours to finally obtain a polymer film composed of crystalline sulfonated polystyrene. b - A proton exchange membrane made of polyimide block copolymer.

[0069] Example 4 (NS5)2- b -(ND) 10 Block copolymer proton exchange membrane

[0070] Under nitrogen protection, S5 (3.0773 g, 0.75 mmol), 1,4,5,8-naphthalenetetracarboxylic anhydride (NTDA) (0.1340 g, 0.5 mmol), benzoic acid (0.1220 g, 1 mmol), isoquinoline (0.1292 g, 1 mmol), and 16 mL of m-cresol were sequentially added to a 100 mL dry three-necked flask. The mixture was mechanically stirred at room temperature for 1 hour, then slowly heated to 80 °C for 4 hours, and then heated to 180 °C for another 4 hours to obtain the amino-terminated hydrophilic block (NS5)2. Subsequently, (ND) synthesized in the previous step was added to the three-necked flask.10 (1.1483 g, 0.25 mmol), benzoic acid (0.0610 g, 0.5 mmol), isoquinoline (0.06460 g, 0.5 mmol), and 10 mL m-cresol. The resulting reaction system was mechanically stirred at room temperature for 1 hour, then slowly heated to 80 °C for 4 hours, and then heated to 180 °C for another 20 hours. After the reaction was complete, the resulting reaction system was cooled to room temperature, and the resulting mixture was stirred at room temperature for 1 hour, then heated to 180 °C for 20 hours. After the reaction was complete, the resulting mixture was cooled to 80 °C and quickly poured into 150 mL of methanol, forming a filamentous precipitate. The precipitate was repeatedly washed with methanol and filtered to collect the solid product. Finally, the solid product was vacuum dried at 100 °C for 20 hours to obtain crystalline sulfonated polyphenylene with an average hydrophobic block length of 10 and a hydrophilic block of (NS5)2. b -Imide block copolymer (NS5)2- b -(ND) 10 .

[0071] (NS5)2- b -(ND) 10 The polymer solution was prepared by dissolving it in m-cresol to a solid content of 5 w / v. After vacuum degassing, the resulting solution was cast onto a clean glass plate and dried in a 110 °C oven for 5 hours to form a polymer film. After drying, the film was peeled off the glass plate and immersed in methanol for 24 hours to remove residual m-cresol. Subsequently, the film was placed in 50 mL of 1.0 M sulfuric acid solution and immersed at room temperature for 72 hours for proton exchange treatment. The proton-exchanged film was washed with deionized water until neutral and then vacuum dried at 120 °C for 20 hours to finally obtain a polymer film composed of crystalline sulfonated polystyrene. b Proton exchange membranes made of α-imide block copolymers.

[0072] Example 5 S 10 - b -(ND) 10 Block copolymer proton exchange membrane

[0073] Under nitrogen protection, S 10 (2.0246 g, 0.25 mmol) and 10 mL of m-cresol were added sequentially to a 100 mL dry three-necked flask and mechanically stirred at room temperature until S 10 Completely dissolve. Then, add the (ND) synthesized in the previous step to the three-necked flask. 10(1.1483 g, 0.25 mmol), benzoic acid (0.0610 g, 0.5 mmol), isoquinoline (0.0646 g, 0.5 mmol), and 11 mL m-cresol. The resulting reaction system was mechanically stirred at room temperature for 1 hour, then slowly heated to 80 °C for 4 hours, and then heated to 180 °C for another 20 hours. After the reaction was complete, the resulting reaction system was cooled to room temperature, and the resulting mixture was stirred at room temperature for 1 hour, followed by heating to 180 °C for 20 hours. After the reaction was complete, the resulting mixture was cooled to 80 °C and quickly poured into 150 mL of methanol, forming a filamentous precipitate. The precipitate was repeatedly washed with methanol and filtered to collect the solid product. Finally, the solid product was vacuum dried at 100 °C for 20 hours to obtain crystalline sulfonated polyphenylene with an average hydrophobic block length of 10 and an average hydrophilic block length of 10. b -Polyimide block copolymer S 10 - b -(ND) 10 .

[0074] S 10 - b -(ND) 10 The polymer solution was prepared by dissolving it in m-cresol to a solid content of 5 w / v. After vacuum degassing, the resulting solution was cast onto a clean glass plate and dried in a 110 °C oven for 5 hours to form a polymer film. After drying, the film was peeled off the glass plate and immersed in methanol for 24 hours to remove residual m-cresol. Subsequently, the film was placed in 50 mL of 1.0 M sulfuric acid solution and immersed at room temperature for 72 hours for proton exchange treatment. The proton-exchanged film was washed with deionized water until neutral and then vacuum dried at 120 °C for 20 hours to finally obtain a polymer film composed of crystalline sulfonated polystyrene. b - A proton exchange membrane made of polyimide block copolymer.

[0075] Example 6 S 10 - b -(ND)8 block copolymer proton exchange membrane

[0076] Under nitrogen protection, 1,4,5,8-naphthalenetetracarboxylic anhydride (NTDA) (2.4136 g, 9 mmol), 1,12-diaminododecane (DDA) (1.6032 g, 8 mmol), benzoic acid (1.9542 g, 16 mmol), isoquinoline (2.0666 g, 16 mmol), and 20 mL of m-cresol were sequentially added to a 100 mL dry three-necked flask. The mixture was stirred at room temperature for 1 hour, then heated to 80 °C for 4 hours, and then heated to 180 °C for another 20 hours. After the reaction was complete, the mixture was cooled to room temperature, and the reaction mixture was slowly poured into 150 mL of methanol, precipitating an orange solid powder. The obtained solid was repeatedly washed with methanol, filtered, and then extracted with acetone until the eluent was colorless. Finally, it was dried under vacuum at 160 °C for 20 hours to obtain a polyimide oligomer (ND)8 with an anhydride-terminated repeating unit length of 8.

[0077] S 10 (2.0246 g, 0.25 mmol) and 10 mL of m-cresol were added sequentially to a 100 mL dry three-necked flask and mechanically stirred at room temperature until S 10 Complete dissolution was achieved. Subsequently, the synthesized (ND)8 (0.9331 g, 0.25 mmol), benzoic acid (0.0610 g, 0.5 mmol), isoquinoline (0.0646 g, 0.5 mmol), and 9.3 mL of m-cresol were added to a three-necked flask. The resulting reaction system was mechanically stirred at room temperature for 1 hour, then slowly heated to 80 °C for 4 hours, and then further heated to 180 °C for 20 hours. After the reaction was complete, the resulting reaction system was cooled to room temperature, and the mixture was stirred at room temperature for 1 hour, followed by heating to 180 °C for 20 hours. After the reaction was complete, the mixture was cooled to 80 °C and quickly poured into 150 mL of methanol, forming a filamentous precipitate. The precipitate was repeatedly washed with methanol and filtered to collect the solid product. Finally, the solid product was vacuum dried at 100 °C for 20 hours to obtain crystalline sulfonated polyphenylene with an average hydrophobic block length of 8 and an average hydrophilic block length of 10. b -Polyimide block copolymer S 10 - b -(ND)8.

[0078] S 10 - b-(ND)8 was dissolved in m-cresol to prepare a polymer solution with a solid content of 5 w / v%. The resulting solution was degassed under vacuum, cast onto a clean glass plate, and dried in a 110 °C oven for 5 hours to form a polymer film. After drying, the film was peeled off the glass plate and immersed in methanol for 24 hours to remove residual m-cresol. Subsequently, the film was placed in 50 mL of 1.0 M sulfuric acid solution and immersed at room temperature for 72 hours for proton exchange treatment. The proton-exchanged film was washed with deionized water until neutral and then vacuum dried at 120 °C for 20 hours to finally obtain a polymer film composed of crystalline sulfonated polystyrene. b - A proton exchange membrane made of polyimide block copolymer.

[0079] Example 6 (S) 10 - b Transmission electron microscopy (TEM) images of -(ND)8) as follows Figure 4 As shown.

[0080] Example 7 S 10 - b -(ND)6 block copolymer proton exchange membrane

[0081] Under nitrogen protection, 1,4,5,8-naphthalenetetracarboxylic anhydride (NTDA) (1.8772 g, 7 mmol), 1,12-diaminododecane (DDA) (1.2024 g, 6 mmol), benzoic acid (1.4657 g, 12 mmol), isoquinoline (1.5500 g, 12 mmol), and 15 mL of m-cresol were sequentially added to a 100 mL dry three-necked flask. The mixture was stirred at room temperature for 1 hour, then heated to 80 °C for 4 hours, and then heated to 180 °C for another 20 hours. After the reaction was complete, the mixture was cooled to room temperature, and the reaction mixture was slowly poured into 150 mL of methanol, precipitating an orange solid powder. The obtained solid was repeatedly washed with methanol, filtered, and then extracted with acetone until the eluent was colorless. Finally, it was dried under vacuum at 160 °C for 20 hours to obtain a polyimide oligomer (ND)6 with an anhydride-terminated repeating unit length of 6.

[0082] S 10 (2.0246 g, 0.25 mmol) and 10 mL of m-cresol were added sequentially to a 100 mL dry three-necked flask and mechanically stirred at room temperature until S 10Complete dissolution was achieved. Subsequently, the synthesized (ND)6 (0.7158 g, 0.25 mmol), benzoic acid (0.0610 g, 0.5 mmol), isoquinoline (0.0646 g, 0.5 mmol), and 9.3 mL of m-cresol were added to a three-necked flask. The resulting reaction system was mechanically stirred at room temperature for 1 hour, then slowly heated to 80 °C for 4 hours, and then further heated to 180 °C for 20 hours. After the reaction, the resulting reaction system was cooled to room temperature, and the mixture was stirred at room temperature for 1 hour, followed by heating to 180 °C for 20 hours. After the reaction, the mixture was cooled to 80 °C and quickly poured into 150 mL of methanol, forming a filamentous precipitate. The precipitate was repeatedly washed with methanol and filtered to collect the solid product. Finally, the solid product was vacuum dried at 100 °C for 20 hours to obtain crystalline sulfonated polyphenylene with an average hydrophobic block length of 6 and an average hydrophilic block length of 10. b -Polyimide block copolymer S 10 - b -(ND)6.

[0083] S 10 - b -(ND)6 was dissolved in m-cresol to prepare a polymer solution with a solid content of 5 w / v%. The resulting solution was degassed under vacuum, cast onto a clean glass plate, and dried in a 110 °C oven for 5 hours to form a polymer film. After drying, the film was peeled off the glass plate and immersed in methanol for 24 hours to remove residual m-cresol. Subsequently, the film was placed in 50 mL of 1.0 M sulfuric acid solution and immersed at room temperature for 72 hours for proton exchange treatment. The proton-exchanged film was washed with deionized water until neutral and then vacuum dried at 120 °C for 20 hours to finally obtain a polymer film composed of crystalline sulfonated polystyrene. b - A proton exchange membrane made of polyimide block copolymer.

[0084] Example 3 (NS5- b -(ND) 10 Example 4 ((NS5)2- b -(ND) 10 Example 5 (S) 10 - b -(ND) 10 Example 6 (S) 10 - b -(ND)8) and Example 7 (S) 10 - b The infrared absorption spectrum of -(ND)6) is as follows: Figure 2 As shown.

[0085] Example 3 (NS5-b -(ND) 10 Example 4 ((NS5)2- b -(ND) 10 Example 5 (S) 10 - b -(ND) 10 Example 6 (S) 10 - b -(ND)8), Example 7 (S) 10 - b X-ray diffraction (XRD) patterns of -(ND)6 and Nafion 212 are as follows: Figure 3 As shown.

[0086] Comparative Example 1 (NB) 15 - b -(ND) 10 Block copolymer proton exchange membrane

[0087] Under nitrogen protection, 1,4,5,8-naphthalenetetracarboxylic anhydride (NTDA) (2.95 g, 11 mmol), 1,12-diaminododecane (DDA) (2.004 g, 10 mmol), benzoic acid (2.687 g, 2.2 mmol), 3.0 mL isoquinoline, and 40 mL m-cresol were sequentially added to a 100 mL dry three-necked flask. The mixture was stirred at room temperature for 1 hour, then heated to 80 °C for 4 hours, and then heated to 180 °C for another 20 hours. After the reaction was complete, the mixture was cooled to room temperature, and the reaction mixture was slowly poured into 150 mL of methanol, precipitating an orange solid powder. The obtained solid was repeatedly washed with methanol, filtered, and then extracted with acetone until the eluent was colorless. Finally, it was dried under vacuum at 160 °C for 20 hours to obtain the anhydride-terminated polyimide oligomer (ND). 10 .

[0088] Under nitrogen protection, 0.846 g (1.6 mmol) of 4,4'-bis(4-aminophenoxy)biphenyl-3,3'-disulfonic acid (BAPBDS), 8.3 mL of m-cresol, and 0.7 mL of triethylamine were sequentially added to a 100 mL dry three-necked flask, and the mixture was mechanically stirred at room temperature until the BAPBDS was completely dissolved. Then, 0.402 g (1.5 mmol) of NTDA, 0.5366 g (3.0 mmol) of benzoic acid, and 0.7 mL of isoquinoline were added sequentially. The resulting reaction mixture was mechanically stirred at room temperature for 1 hour, then slowly heated to 80 °C for 4 hours, and then further heated to 180 °C for 20 hours. After the reaction was complete, the resulting reaction mixture was cooled to room temperature, and the (ND) synthesized in the previous step was added to the three-necked flask. 10(0.4593 g, 0.1 mmol) and 3 mL of m-cresol were added. The resulting mixture was stirred at room temperature for 1 hour, followed by heating to 180 °C and reacting for 20 hours. After the reaction was complete, the resulting mixture was cooled to 80 °C and quickly poured into 150 mL of methanol, forming a filamentous precipitate. The precipitate was repeatedly washed with methanol and filtered to collect the solid product. Finally, the solid product was vacuum dried at 100 °C for 20 hours to obtain a crystalline sulfonated polyimide block copolymer (NB) with an average hydrophobic block length of 10 and an average hydrophilic block length of 15. 15 - b -(ND) 10 .

[0089] (NB) 15 - b -(ND) 10 The polymer solution was prepared by dissolving it in m-cresol to a solid content of 5 w / v. After vacuum degassing, the resulting solution was cast onto a clean glass plate and dried in a 110 °C oven for 5 hours to form a polymer membrane. After drying, the membrane was peeled off the glass plate and immersed in methanol for 24 hours to remove residual m-cresol. Subsequently, the membrane was placed in 50 mL of 1.0 M sulfuric acid solution and immersed at room temperature for 72 hours for proton exchange treatment. The proton-exchanged membrane was washed with deionized water until neutral and then vacuum dried at 120 °C for 20 hours to finally obtain a proton exchange membrane made of crystalline sulfonated polyimide block copolymer.

[0090] Experimental Example 1: Oxidative Stability and Hydrolytic Stability Test

[0091] The oxidative stability of the proton exchange membranes prepared in Examples 3-7 and Comparative Example 1 was determined by their initial dissolution time in Fenton's reagent (80°C, 3% H₂O₂, 3 ppm FeSO₄). 1 and complete dissolution time 2. The characterization was performed, and the results are shown in Table 1.

[0092] As shown in Table 1, the membranes of Examples 3-7 exhibited initial dissolution times in Fenton's reagent exceeding 160 minutes, significantly better than Comparative Example 1 (sulfonated polyimide), which had an initial dissolution time of 117 minutes. Examples 3-7 demonstrated excellent oxidative stability due to the use of sulfonated polyphenylene oligomers as hydrophilic blocks.

[0093] In a pressurized, sealed autoclave, a thickness of 30... Each membrane sample was placed in water at 140 °C for 24 hours. The quality of the samples before and after treatment and in their dried state was assessed to evaluate hydrolytic stability.

[0094] As shown in Table 1, after accelerated hydrolysis stability testing, the mass loss of the membranes in Examples 3-7 was over 98% of the initial mass. Compared to Comparative Example 1, the mass retention rate of Examples 3-7 increased by 2.0-2.7%, indicating that the sulfonated polyphenylene... b - Polyimide membranes exhibit high hydrolytic stability.

[0095] Experimental results show that the sulfonated polyphenylene oligomers of the present invention, as hydrophilic blocks, not only effectively maintain the properties of sulfonated polyphenylene- b - The hydrolytic stability of the polyimide proton exchange membrane is improved, while its resistance to free radical oxidation is also enhanced.

[0096] Table 1. Anti-radical oxidation stability and hydrolytic stability of proton exchange membranes

[0097] Experimental Example 2: Testing of water absorption rate, swelling rate, ion exchange capacity and proton conductivity

[0098] Each proton exchange membrane sample was cut into a rectangle (8cm). 3 cm), after complete drying, weigh the membrane. W d ), and simultaneously measure the thickness of the membrane ( t d ) and planar dimensions ( l d Then, the membrane was soaked in deionized water for 12 hours. After removal, the surface moisture of the membrane was blotted dry with lint-free paper, and the mass of the membrane after water absorption and swelling was quickly weighed. W w ), and measure the thickness of the proton exchange membrane ( t w ) and planar dimensions ( l w Water absorption rate () WU ), thickness direction swelling ratio ( t ) and planar swelling ratio ( l The following formulas are used to calculate the values ​​respectively:

[0099] Accurately weigh 0.2–0.3 g of each dried proton exchange membrane sample, cut it into small pieces, and place it in 50 mL of saturated sodium chloride solution. Stir at room temperature for 3 days. Then remove the membrane and wash it three times with a small amount of deionized water. Collect all eluent and combine it with the original saturated sodium chloride solution. Titrate with a sodium hydroxide solution of known concentration to determine the H+ content in the solution. + Content. Ion exchange capacity (IEC) is calculated using the following formula:

[0100] in, C NaOH The concentration of the NaOH solution is expressed in mmol / L. V NaOH The volume of NaOH solution consumed during the titration process (unit: L). m This represents the mass of the membrane (unit: g).

[0101] The proton conductivity of the proton exchange membranes in Examples 3-7, Comparative Example 1, and Nafion 212 was measured using the AC impedance method. A Hiokki 3553 Hitester AC impedance meter was used, and the test conditions were as follows: test frequency 42 Hz-5 MHz; test medium: ultrapure water; test temperature: 40 ℃ or 80 ℃. Proton conductivity (Unit: S / cm) Calculated according to the following formula:

[0102] in, D The distance between the two electrodes is 5 mm. L The width of the membrane sample is 5 mm. B For the thickness of the membrane sample (30-50) m), R To test the impedance of the sample (unit: ).

[0103] Table 2. Water absorption rate, swelling ratio, ion exchange capacity and proton conductivity of proton exchange membranes

[0104] As can be seen from Table 2, with the hydrophilic block as S 10 Taking Examples 5-7 as examples, as the IEC increased from 1.83 meq / g to 2.20 meq / g, the water absorption rate of the samples increased from 35% (Example 5) to 43% (Example 7), while the planar / thickness swelling ratio increased from 4% / 32% to 5% / 38%. This indicates that the increase in IEC is beneficial to the construction of the hydration network, but it also exacerbates the size expansion of the membrane. Further comparison with Examples 4 and 6, which have similar IEC values, shows that although both IEC values ​​are approximately 2.04 meq / g, the hydrophilic block in Example 6 has a longer phenylene s-type structure. 10Furthermore, it contains no imide rings, resulting in stronger π-π interactions between its hydrophilic backbone and a clearer microphase separation structure. Consequently, the water absorption rate of Example 6 is only 38%, and the planar / thickness swelling rates are controlled at 4% / 34%, respectively. This performance is not only comparable to commercial Nafion 212 (water absorption rate ≈ 40%), but also significantly lower than the 63% water absorption rate and 6% / 59% swelling rate of Example 4. These results clearly demonstrate that by extending the length of the hydrophilic polyphenylene backbone and optimizing the phase separation structure, it is possible to effectively suppress membrane expansion while maintaining high IEC, thereby achieving a synergistic balance between high ion exchange capacity and low dimensional deformation.

[0105] As can be seen from Table 2, the sulfonated polyphenylene in Examples 3-7... b - Polyimide proton exchange membranes have a higher ion exchange capacity than Nafion 212. Furthermore, the sulfonated polyphenylene in Examples 3-7... b - The polyimide block copolymer proton exchange membrane exhibited higher proton conductivity than Nafion 212 at both 40 °C and 80 °C, with Example 7 (S) 10 - b The proton conductivity of -(ND)6 is 0.184 S / cm (80 °C).

[0106] Experimental Example 3: Power Generation Performance Test

[0107] Preparation method of membrane electrode (MEA): Using 40wt% Pt / C (Johnson) as the electrode catalyst and Nafion as the binder, a catalyst ink was prepared and uniformly sprayed onto both sides of each proton exchange membrane sample, with an effective area of ​​5 cm² on each side. 2 The platinum catalyst loadings at the anode and cathode were 0.3 mg / cm³, respectively. 2 and 0.7 mg / cm 2 .

[0108] The power generation performance of the single cells assembled with Nafion 212 membrane in Example 6 was tested using a Scribner 850e fuel cell test equipment (USA). The test conditions were as follows: (1) Polarization curve test gas supply: the flow rates of hydrogen and oxygen were both 100 mL / min; Durability test gas supply: the flow rates of hydrogen and oxygen were both 25 mL / min; (2) Test temperature: 90 ℃; (3) Back pressure: 150 kPa; (4) Humidification conditions: the relative humidity of the gas was 100% and 30%, respectively.

[0109] The results are shown in Figure 5. Compared to the single cell assembled with the Nafion 212 proton exchange membrane, the sulfonated polyphenylene prepared in Example 6... bThe single cell assembled with a polyimide block copolymer proton exchange membrane not only has a higher open-circuit voltage (1.046 V), but also an improved peak power density, indicating that the membrane has superior electrochemical performance and energy output characteristics in the field of fuel cells.

[0110] Figure 5-1 The display shows that under high relative humidity conditions (90 °C, 100%RH), the current density is below 1000 mA / cm². 2 At that time, the power generation performance of the single cell assembled in Example 6 was comparable to that of the single cell assembled with Nafion polymer. However, at higher current densities, the power generation performance of the single cell assembled in Example 6 was further improved, and the resistance decreased, indicating that it has superior conductivity and energy conversion efficiency under high load conditions. Test results show that at a current density of 4.2 A / cm 2 At that time, the peak power density of the single cell assembled in Example 6 reached 2.01 W / cm². 2 Nafion polymer-assembled single cells achieve 3.2 A / cm². 2 The peak power density at that time was only 1.59 W / cm³. 2 Therefore, the peak power density of the single cell assembled in Example 6 is 26% higher than that of the single cell assembled with Nafion polymer.

[0111] Figure 5-2 The polarization curves of the single cells assembled in Example 6 and Nafion 212 are shown under conditions of 90 °C and low relative humidity (30% RH). The test results indicate that under these conditions, the peak power density of the single cell assembled in Example 6 is 1.32 W / cm². 2 (Corresponding current density 2.74 A / cm) 2 The peak power density of a single cell assembled from Nafion 212 is 0.93 W / cm². 2 (Corresponding current density 2.1 A / cm) 2 Therefore, the peak power density of the single cell assembled in Example 6 is approximately 42% higher than that of the single cell assembled in Nafion 212.

[0112] The above results indicate that the sulfonated polyphenylene prepared in Example 6... b The single cell assembled with a polyimide block copolymer proton exchange membrane exhibits superior power generation performance compared to the single cell assembled with Nafion 212 under both high and low humidity conditions, further demonstrating the applicability of the membrane material of the present invention in different humidity environments, reducing dependence on external humidification systems, thereby improving the energy efficiency ratio and overall operational stability of the fuel cell system.

[0113] Experimental Example 4: Durability Test

[0114] The stability of the proton exchange membrane (PEM) was evaluated by open-circuit voltage (OCV) durability testing under conditions of 90 °C and 50% RH. The results are as follows: Figure 6 As shown.

[0115] Test results show that the single cell assembled in Example 6 exhibited O2 levels during a 452-hour continuous test. C The OCV decreased from 1.046 V to 0.998 V, with a decay rate of 0.11 mV / h. In contrast, a single cell assembled with Nafion 212 showed an OCV decrease from 1.032 V to 0.905 V during 91.5 hours of continuous testing, with a decay rate of 1.39 mV / h. This indicates that the proton exchange membrane of Example 6 exhibits excellent durability and chemical stability under these conditions. Further analysis shows that the sulfonated polyphenylene oxide provided by this invention... b - Polyimide block copolymer proton exchange membranes can effectively suppress performance degradation caused by hydrolysis or oxidation during long-term operation, thereby improving the stability and service life of fuel cells.

[0116] Experimental Example 5: Mechanical Performance Testing

[0117] Figure 7 Example 3 (NS5-) b -(ND) 10 Example 4 ((NS5)2- b -(ND) 10 Example 5 (S) 10 - b -(ND) 10 Example 6 (S) 10 - b -(ND)8), Example 7 (S) 10 - b -(ND)6) stress-strain curves. The tensile strength of all embodiments exceeds 60 MPa, and the elongation at break exceeds 30%. Where S 10 - b -(ND)8 has a tensile strength of 78 MPa and an elongation at break of 40%. These data indicate that the sulfonated polyphenylene oxide prepared by the block copolymerization strategy... b Polyimide possesses both high resistance to stress damage and high toughness, meeting the mechanical performance requirements during membrane electrode assembly (MEA) assembly.

[0118] The sulfonated polyphenylene provided by this invention b -Polyimide proton exchange membrane S 10 - b-(ND)8 exhibits superior overall performance compared to existing sulfonated polyimide, sulfonated polyphenylene, and Nafion 212 membranes in key performance indicators such as proton conductivity, power generation performance, hydrolysis and oxidation stability, mechanical strength, and dimensional stability, making it suitable for use in fuel cell systems under high temperature and low humidity conditions. Typical performance indicators are as follows: 1. Proton conductivity Under conditions of 80 °C and 100% RH, S 10 - b The proton conductivity of the -(ND)8 membrane can reach 0.173 S / cm, which is better than that of Nafion 212 (0.160 S / cm).

[0119] 2. Membrane electrode power generation efficiency

[0120] S 10 - b The peak power density of the (ND)8 assembled single cell reaches 2.01 W / cm². 2 (90 ℃, 100% RH, 150kPa), 1.31 W / cm 2 (90 ℃, 30% RH, 150 kPa), while the peak power density of Nafion polymer-assembled single cells is only 1.58 W / cm². 2 (90 ℃, 100% RH, 150 kPa), 0.93 W / cm 2 (90 ℃, 30% RH, 150 kPa).

[0121] 3. Hydrolytic stability

[0122] After aging in distilled water at 120℃ for 24 h, S 10 - b The (ND)8 membrane maintained a quality retention rate of over 98%, which is higher than that of Comparative Example 1 (NB). 15 - b -(ND) 10 (Quality retention rate 96%).

[0123] 4. Oxidative stability

[0124] S 10 - b The initial dissolution time of the -(ND)8 membrane in Fenton's reagent (80 °C, 3% H2O2, 3 ppm FeSO4) was 180 minutes, which was longer than that of Comparative Example 1 (NB). 15 - b -(ND) 10 (Initial dissolution time: 117 minutes).

[0125] 5. Mechanical properties

[0126] S 10 - b The (ND)8 membrane has a tensile strength of 78 MPa and an elongation at break of 40%, making it suitable for MEA processing. It also maintains good toughness even when absorbing water, making it suitable for practical assembly requirements.

[0127] 6. Swelling rate and dimensional stability

[0128] S 10 - b The volume swelling rate of the (ND)8 membrane in water at 25 °C was controlled at 45%, which is lower than that of Nafion 212 (52%).

[0129] 7. Film thickness uniformity and film-forming properties

[0130] It is suitable for solution casting processes, producing films with uniform thickness (30-40 μm), smooth surface, no obvious defects, and is ready for mass production.

[0131] The preferred embodiments of the present invention have been described in detail above. It should be understood that those skilled in the art can make numerous modifications and variations based on the concept of the present invention without creative effort. Therefore, all technical solutions that can be obtained by those skilled in the art based on the concept of the present invention through logical analysis, reasoning, or limited experimentation on the basis of existing technology should be within the scope of protection defined by the claims.

Claims

1. An amino-terminated sulfonated polyphenylene oligomer, the structural formula of which is shown in formula (1): Equation (1) in, R1 represents an aromatic substituent containing at least one sulfonic acid group (-SO3H) or its salt form, wherein the aromatic substituent comprises a carbonyl group (-CO-) and / or a sulfonyl group (-SO2-). R2 and R3 represent monovalent groups, which are selected from hydrogen, halogen, alkyl or substituted alkyl, aryl or substituted aryl; x is an integer from 1 to 100, representing the number of repeating units; y is an integer from 1 to 4, representing the number of R2 groups in the benzene ring.

2. The amino-terminated sulfonated polyphenylene oligomer according to claim 1, wherein, At least one of the following must be met: R1 is selected from any one of the following groups: , , , , , , , ; R2 is selected from any one of the following groups: -H, -CH3, -CF3; R3 is selected from any of the following groups: -H, -CH3, -F.

3. A method for preparing the amino-terminated sulfonated polyphenylene oligomer according to claim 1 or 2, comprising the following steps: Step 1): Sulfonated dibromobiphenyl compound containing carbonyl or sulfonyl groups, diboronic acid compound or its esterified derivative, end-capping agent containing amino groups, base, palladium (Pd) catalyst, organic solvent and water are added sequentially to a three-necked flask and reacted at 20~150 °C for 1~30 hours. The reaction process is shown in reaction formula (1) to obtain amino-terminated polyphenylene oligomers with sulfonated aromatic side chains. Step 2): After cooling the reaction system to room temperature, remove some of the solvent under reduced pressure. Add the concentrated solution dropwise to a poor organic solvent to induce product precipitation. After washing with the poor solvent and centrifugation, dry under vacuum at 10–100 °C. The resulting solid is dissolved in a mixed solvent and then subjected to H₂O₂… + Amberlite cation exchange resin was used for cation exchange to obtain a sulfonic acid polymer; the filtrate was collected after vacuum filtration, and an organic base was added dropwise to the filtrate to obtain a sulfonated triethylamine salt polymer; most of the solvent in the resulting reaction solution was removed by vacuum distillation, and the concentrate was added dropwise to a poor organic solvent. The precipitated solid was washed, centrifuged, and then vacuum dried at 10-100 °C for 12 hours to obtain the amino-terminated sulfonated polyphenylene oligomer. Reaction formula (1) in, R1 represents an aromatic substituent containing at least one sulfonic acid group (-SO3H) or its salt form, wherein the aromatic substituent comprises a carbonyl group (-CO-) and / or a sulfonyl group (-SO2-). R2 and R3 represent monovalent groups, which are selected from hydrogen, halogen, alkyl or substituted alkyl, aryl or substituted aryl; x is an integer from 1 to 100, representing the number of repeating units; y is an integer from 1 to 4, representing the number of R2 groups in the benzene ring; R4 represents a monovalent group, which is selected from boric acid groups or their esterified, salted, or coordinated derivatives.

4. The preparation method according to claim 3, wherein, At least one of the following must be met: R4 is selected from one or more of the following groups: , , , , ; In step 1), the diboronic acid compound or its esterified derivative is selected from one or more of the following: terephthaloboronic acid, pinacol terephthalate, ethylene glycol terephthalate, catechol terephthalate, propylene glycol terephthalate, isophthaloboronic acid, pinacol terephthalate, pinacol terephthalate, phthaloboronic acid, (2-methyl-1,4-phenyl)diboronic acid, (2-methyl-1,4-phenyl)diboronic acid dipinacol ester, and 5-(trifluoromethyl)benzene-1,3-diboronic acid; In step 1), the amino-containing capping agent is selected from one or more of 4-aminophenylboronic acid salt, 4-aminophenylboronic acid pinacol ester, 4-aminophenylboronic acid, 3-aminophenylboronic acid pinacol ester, 3-aminophenylboronic acid, and 2-fluoro-5-aminophenylboronic acid. In step 1), the organic solvent is selected from... N , N -Dimethylacetamide, N , N -Dimethylformamide, N One or more of the following: methylpyrrolidone, dimethyl sulfoxide, methanol, ethanol, tetrahydrofuran, and toluene; In step 1), the palladium (Pd) catalyst is selected from one or more of Pd(OAc)2, Pd(PPh3)4, and Pd(dppf)Cl2; In step 1), the base is selected from one or more of Na2CO3, K2CO3, K3PO4, triethylamine, tetramethylammonium hydroxide, and tetrabutylammonium hydroxide; In step 1), the palladium (Pd) catalyst may or may not use a ligand, wherein the ligand is selected from one or more of PPh3, n-Bu3P, 1,2-bis(diphenylphosphine)ethane, 1,3-bis(diphenylphosphine)propane, and 1,1'-bis(diphenylphosphine)ferrocene; the molar ratio of the ligand to a sulfonated dibromobiphenyl compound containing a carbonyl or sulfonyl group is 0:1 to 1:1; In step 1), the molar ratio of the base to the sulfonated dibromobiphenyl compound containing a carbonyl or sulfonyl group is 0:1 to 20:1; the molar ratio of the Pd catalyst to the sulfonated dibromobiphenyl compound containing a carbonyl or sulfonyl group is 0:1 to 1:1; the volume ratio of the organic solvent to water is 0:1 to 100:1; and the solid content of the reaction system is 0.1 to 100 w / v%. In step 2), the H in the Amberlite ion exchange resin + The molar ratio of the sulfonic acid group to the sulfonic acid group is 1:1 to 20:1; the solid content of the reaction solution is 0.1 to 100 w / v%. In step 2), the organic base is selected from one or more of triethylamine, tetramethylammonium hydroxide, and tetrabutylammonium hydroxide; In step 2), the molar ratio of the organic solvent to water in the mixed solvent is 0:1 to 100:1, and the organic solvent is selected from... N , N -Dimethylacetamide, N , N -Dimethylformamide, N One or more of the following: methylpyrrolidone, dimethyl sulfoxide, methanol, ethanol, tetrahydrofuran, and toluene; In step 2), the organic poor solvent is selected from one or more of acetone, isopropanol, ethyl acetate, methanol, ethanol, tetrahydrofuran, and toluene.

5. A sulfonated polyphenylene- b - A polyimide copolymer, the structural formula of which is represented by Formula 2: (Equation 2) in, R1 represents an aromatic substituent containing at least one sulfonic acid group (-SO3H) or its salt form, wherein the aromatic substituent comprises a carbonyl group (-CO-) and / or a sulfonyl group (-SO2-). R2 and R3 represent monovalent groups, which are selected from hydrogen, halogen, alkyl or substituted alkyl, aryl or substituted aryl; x is an integer from 1 to 100, representing the number of repeating units; y is an integer from 1 to 4, representing the number of R2 groups in the benzene ring; m and n are integers from 1 to 100, representing the number of repeating units; Ar1 represents a tetravalent group, which is selected from naphthyl or naphthalene derivatives; R5 represents a divalent group, which is selected from aliphatic groups, aromatic groups, or aromatic-aliphatic groups.

6. The sulfonated polyphenylene according to claim 5 b - Polyimide copolymer, wherein R5 is selected from any one of the following groups: , , , , , ; and / or Ar1 is selected from any one of the following groups: , , 。 7. The sulfonated polyphenylene according to claim 5 or 6 b The preparation method of the polyimide copolymer includes the following steps: Step (1): Ar1 type dianhydride monomer, hydrophobic R5 type diamine monomer, catalyst and phenolic good solvent are added to a three-necked flask and heated to 50~140 ℃ for 1~10 hours. The reaction temperature is then increased to 150~200 ℃ for 2~30 hours. After the resulting reaction system is cooled to room temperature, it is added dropwise to an organic poor solvent to promote the precipitation of the product. After washing with the poor solvent and centrifugation, it is vacuum dried at 10~200 ℃ to obtain anhydride-terminated polyimide oligomer. The reaction process is shown in reaction formula (2): Reaction formula (2); Step (2): The amino-terminated sulfonated polyphenylene oligomer, the anhydride-terminated polyimide oligomer, the catalyst, and a good phenolic solvent are added to another three-necked flask. The mixture is heated at 50-140 °C for 1-10 hours. Subsequently, the temperature is increased to 150-200 °C, and the reaction continues for 2-30 hours. After the resulting reaction system is cooled to room temperature, a poor organic solvent is added dropwise to promote the precipitation of the product. After washing with the poor solvent and centrifugation, the product is dried under vacuum at 10-200 °C to obtain sulfonated polyphenylene- b - Polyimide block copolymer, the reaction process is shown in reaction formula (3): Reaction formula (3).

8. The preparation method according to claim 7, wherein, At least one of the following must be met: In steps (1) and (2), the organic poor solvent is selected from one or more of methanol, ethanol, isopropanol, acetone or ethyl acetate; In step (1), the molar ratio of the Ar1 type dianhydride monomer to the hydrophobic R5 type diamine monomer is greater than 1; in step (2), the molar ratio of the amino-terminated sulfonated polyphenylene oligomer to the anhydride-terminated polyimide oligomer is equal to 1. In steps (1) and (2), the phenolic solvent is selected from one or more of m-cresol, o-cresol, p-cresol, m-chlorocresol, o-chlorocresol, or p-chlorocresol; In steps (1) and (2), the catalyst is selected from one or more of acetic acid, benzoic acid, chlorobenzoic acid, hydroxybenzoic acid, quinoline, isoquinoline or pyridine; In step (1), the solid content of the anhydride-terminated polyimide oligomer in a good phenolic solvent is 5~40 w / v%. In step (2), the sulfonated polystyrene- b The solid content of the polyimide block copolymer in good phenolic solvents is 0.5~25 w / v.

9. A proton exchange membrane, wherein, The sulfonated polyphenylene described in claim 5 or 6 b A film was prepared from a polyimide block copolymer, and the film was subjected to proton exchange treatment to obtain a film composed of sulfonated polyphenylene- b - A proton exchange membrane made of polyimide block copolymer.

10. The application of the proton exchange membrane according to claim 9 in a battery.